2010
DOI: 10.1130/b30102.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the provenance of loess and desert sediments in northern China using U-Pb dating and morphology of detrital zircons

Abstract: Chinese loess is regarded as one of the most detailed and long-term archives of climate on land. However, there is still signifi cant controversy over the deposit's origin, limiting interpretation of the sedimentological and paleoclimatic mechanisms responsible for its emplacement. Here this is addressed through morphology and the fi rst laser ablationinductively coupled plasma-mass spectrometer (LA-ICP-MS) U-Pb ages of detrital zircons from loess (last glacial age; northern Loess Plateau). These are compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 65 publications
1
113
1
4
Order By: Relevance
“…Compared with the average signal provided by Nd, Sr, Pb isotopes, age spectra of zircon have advantages reflecting the multiple stages of rock forming in the source regions. Xie et al [48] and Stevens et al [49] found that the distributions of zircon age between several deserts in North China differ significantly and have potential to distinguish the PSAs of Asian dust. There are also some limitations when applying zircon age distribution as source tracer of Asian dust: (1) Picking and measurement of zircon is time-consuming.…”
Section: Geochemistry Of Monomineralmentioning
confidence: 99%
“…Compared with the average signal provided by Nd, Sr, Pb isotopes, age spectra of zircon have advantages reflecting the multiple stages of rock forming in the source regions. Xie et al [48] and Stevens et al [49] found that the distributions of zircon age between several deserts in North China differ significantly and have potential to distinguish the PSAs of Asian dust. There are also some limitations when applying zircon age distribution as source tracer of Asian dust: (1) Picking and measurement of zircon is time-consuming.…”
Section: Geochemistry Of Monomineralmentioning
confidence: 99%
“…Throughout the Quaternary, dust emissions from these regions, which include the Tarim Basin, the northeastern Qinghai-Tibetan Plateau (Honda et al, 2004;Stevens et al, 2010;Pullen et al, 2011), the Ala Shan Plateau, and the Southern Gobi Desert of Mongolia (Sun et al, 2000(Sun et al, , 2002a, have been the source of the material transported to form vast accumulations of dust such as those on the Chinese Loess Plateau (Liu, 1985). Transported materials provide evidence concerning atmospheric circulation patterns as well as dust traces in ice cores in Arctic regions (Bory et al, 2002(Bory et al, , 2003,and have been used as proxies for past climate changes (Hao and Guo, 2005;Bloemendal et al, 2008;Sun et al, 2008Sun et al, , 2010 in depositional areas.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, Guo Z. T. et al (2001)'s work was only performed in one section, so it remains to be explored if similar observations can be found for other lower red-clay sediments of similar age at different locations on the CLP. Zircon U-Pb age distribution patterns have proven to be particularly useful for tracing the provenance of Chinese loess (Stevens et al, 2010;Pullen et al, 2011). We have generated some zircon U-Pb ages (Nie et al, 2014a) from the Chaona red-clay section (Figure 1).…”
Section: Debates About Origins Of the Red-clay Sequencementioning
confidence: 99%